Growth and histology of a human mammary-carcinoma cell line at different sites in the athymic mouse. - Levy, J. A. (Nature Publishing Group, 1982)
Experiments were conducted to determine whether the histological pattern of tumour growth of hormone-responsive MCF-7 human mammary adenocarcinoma varied in different tissues of athymic mice. Tumours in the uterus following intrauterine injection were rapidly proliferating and highly invasive. Tumours injected intracerebrally were also highly invasive. In contrast, s.c. tumours and those which arose in the lung following intrapleural injection, grew as small localized nodules without evidence of aggressive invasion of surrounding tissues. These findings indicate that selective implantation of human tumours in athymic mice can be used to develop different models of tumour growth and aggressiveness. IMAGES: